Assessment of Right Ventricular Function before and after Primary Percutaneous Coronary Intervention in Patients with Acute Inferior Wall ST-elevation Myocardial Infarction by Tissue Doppler Imaging - V. S. R. Bhupal; P. Sampath Kumar (Research in Cardiovascular Medicine)
Background: Assessing right ventricular performance using two-dimensional (2D) echocardiography has been difficult due to its complex shape. Tissue Doppler imaging was used as a noninvasive method in this study to evaluate right ventricular function in patients with acute inferior wall ST-elevation myocardial infarction (IWMI) treated with primary percutaneous coronary intervention (PCI). Materials and Methods: Forty patients with IWMI admitted to a tertiary care hospital in India were included in this prospective, observational study. The patient’s detailed history, physical examination along with laboratory parameters, electrocardiogram, echocardiogram, and coronary angiogram profile were recorded from which the decision for PCI was made. The follow-up period for each patient was 6 weeks, during which 2D color Doppler and pulse-wave echocardiographic parameters were assessed. Results: This study comprised 40 patients, among which 16 patients had right ventricular myocardial infarction (RVMI), and the mean age of RVMI patients was 56.65 ± 12.03 years. In RVMI patients, tricuspid annular plane systolic excursion (mm) and RV FAC (%) values were lower than in IWMI patients, and a surge in its respective value to 15.66 ± 1.20 and 32.64 ± 3.17 (P = 0.03) was observed post-PCIs. Furthermore, an inclination in tissue annular systolic velocity (Sm; cm/s) to 11.24 ± 1.55, P = 0.02, and early diastolic tissue annular velocity (Em; cm/s) to 10.98 ± 1.27, P = 0.003, from the baseline was observed after revascularization. The myocardial performance index value accounted to be higher in RVMI patients; however, after PCI, a change from 0.73 ± 0.06 to 0.61 ± 0.12 was noted (P = 0.002). Conclusion: In this study, a significant difference in the echocardiographic parameters assessing RV function in RVMI and IWMI patients was noted, and hence, it can be considered a reliable diagnostic tool to predict the RV performance.